Alternatif Strategi Pengelolaan Sampah Berbasis Pemberdayaan Masyarakat Melalui Bank Sampah Di Desa Tunjuk, Tabanan - Luh Gede Mita Laksmi Susanti; Ni Nyoman Juwita Arsawati (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2021)
The waste problem is a classic polemic that does not end in society. The problem in waste management in Tunjuk Village, Tabanan is quite serious, where the community's awareness and concern for household waste management are still lacking. People still litter and burn rubbish. The purpose of this activity is to provide ideas for community empowerment with alternative solutions in the form of household waste management education. The method used is counseling and poster distribution. Counseling on waste management education uses the SOS method (sort out, saved) with the 3R principle (reduce, reuse, and recycle) and understands the role of waste banks. Then proceed with the distribution of waste management posters with the 3R concept. The result of community service is to increase the motivation of the villagers and change their mindset regarding awareness of being more concerned about the environment and it is hoped that they will immediately make an agreement with village officials to form a waste bank to minimize the presence of waste generation. The idea of ​​forming a waste bank is to help solve the problem of household waste in Tunjuk Village, in order to raise awareness in waste management to obtain direct benefits, both economically and environmental health.